Optimalisasi Pembelajaran Fisika dengan PhET Simulation: Studi Kuantitatif pada Siswa SMA - Nurulfajri, Hazmi; Lestari, Isti Fuji; Warliani, Resti (Universitas Garut, 2024)
This study aims to evaluate the effectiveness of using PhET Simulation in improving students' learning outcomes on the topic of heat and temperature. The research employed a quantitative method with a one-group pretest-posttest design. The subjects were 25 eleventh-grade science students from a senior high school in Garut Regency. Data were collected through multiple-choice tests administered before (pretest) and after (posttest) the learning process using PhET Simulation. The results showed an increase in the average score from 48.08 in the pretest to 64.56 in the posttest. A Paired T-Test statistical analysis revealed a significant difference, with a significance value of 0.002. Additionally, the Cohen’s d effect size of -0.694 indicated a moderate impact. These findings suggest that PhET Simulation is effective in helping students comprehend abstract physics concepts through a visual and interactive approach. The use of this media also enhances student engagement and motivation in the learning process. Based on these results, PhET Simulation is recommended for wider adoption as an innovative learning tool to support students' mastery of physics concepts. This study makes an important contribution to integrating technology into 21st-century education to create more relevant and engaging learning experiences.